2020
DOI: 10.1007/s12639-020-01284-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ticks (Acari: Ixodidae) and Theileria lestoquardi in sheep at El Huda and El Nuhud animals production research stations, Sudan

Abstract: A cross-sectional study was performed 200 blood samples and 314 tick samples in El Huda and El Nuhud animals production research stations, Sudan, in May (summer) and December (winter) in 2016, to determine the prevalence of Theileria lestoquardi in sheep and the potential risk factors associated with the infection. A total of 200 blood samples and 314 tick samples were collected from El Huda (n = 103 blood, 97 tick) and El Nuhud (n = 97 blood, 217 tick) stations. Data on the risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…Regarding sex as a studied individual variable factor, this study found that the overall prevalence of blood parasites in male sheep was significantly higher compared to females, which aligns with earlier studies conducted nationally or internationally ( 63 – 66 ). However, the present findings are in contrast with another reports in Egypt ( 31 , 33 , 62 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding sex as a studied individual variable factor, this study found that the overall prevalence of blood parasites in male sheep was significantly higher compared to females, which aligns with earlier studies conducted nationally or internationally ( 63 – 66 ). However, the present findings are in contrast with another reports in Egypt ( 31 , 33 , 62 ).…”
Section: Discussionsupporting
confidence: 89%
“…was higher in cold season (44.6% and 21.4%, respectively) than in hot season (11.4% and 4.5% respectively). Similarly, another previous study detected higher prevalence of blood parasites in winter when compared to summer ( 63 ). The obtained result disagreed with those data recorded ( 4 ) in Behera governorate (Lower Egypt), who reported higher infection rate in summer months as compared to winter season.…”
Section: Discussionsupporting
confidence: 55%
“…In a study by(Al- HamidhiWeir et al 2016) respectively. The results of the present study on the determination of Theileria species with the results of similar studies indicate the high sensitivity of molecular methods compared to microscopic method(Magzoub et al 2021).…”
supporting
confidence: 78%
“…annulate and Th. lestoquardi from domestic animals in Sudan [ 31 , 32 ]. Other studies reported that Th.…”
Section: Discussionmentioning
confidence: 99%